Growth mechanisms of phthalocyanine nanowires induced by Au nanoparticle templates - Krauss, Tobias Niko; Barrena, Esther; Lohmüller, Theobald; Spatz, Joachim P.; Dosch, Helmut (Physical chemistry, chemical physics, 2011)
We combine X-ray reflectivity and scanning electron microscopy measurements to investigate the mechanisms involved in the growth of vertical arrays of phthalocyanine nanowires directed by templates of Au nanoparticles. The study has been carried out for H16CuPc at different substrate temperatures. It is shown that three organic morphologies evolve during the growth: 1D nanostructures on top of the Au nanoparticles, a multilayer film on the substrate and a layer wetting the gold nanoparticles. For substrate temperatures below 100 °C there is a coexisting and competing growth of the three structures, whereas beyond this temperature the 1D growth on the nanoparticles is predominantly favored. The observance of two regimes with the temperature is characterized by two different activation energies. Both the length of the 1D structures and the thickness of the multilayer film can be precisely controlled by the substrate temperature which is of importance for application of vertical organic nanowires as donor/acceptor architecture in organic solar cells.
Gesehen am 08.07.2022